Economic Development of Former Yugoslav Countries - Saša Kresojević (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Kotor, Montengero, 10-11 September 2015, 2015)
In this paper, it will be discussed about economic development of former Yugoslav countries before and after the war (1990-1995) in those countries. Before the war, Socialist Federal Republic Yugoslavia has performed well until death (1980) of Yugoslavian leader Tito. The peak of living standard in Yugoslavia in that time was in 1979, with Gross domestic product per capita converted in 2013 year value of money was 10,090. Many citizens in SFRY remember that period as “old good days”, but there was significant disparity in GDP per capita between six republics. GDP per capita in economically strongest republic Slovenia was higher than GDP per capita in weakest country Bosnia and Herzegovina for 191.3%, After Tito's death SFRY was performing constant negative growth. After the war, six republics left into transition process which has resulted with private owned economy with concept of liberalism. Nowadays, highest average GDP in those countries was in 2008, year before than world economic crisis came, with value of 11,064 converted and in 2013 it was 9,174 converted .
Keywords: P52; 330; economic development; war; GDP per capita; real growth; living standard